(untitled) (ҚазҰУ хабаршысы. Шығыстану сериясы, 2018)
The article analyzes significance of one of the archeological monuments of the Turkic time discovered in the Central region of Mongolia, at the place called Shoroon Bumbaghar located about 300 km to the west from Ulaan-Baator. Based on his own translation of the epitaph in Chinese scripts carved on the black grave stone and buried in the burial mound (kurgan), which is symbolic burial place without remains of a person’s skeletons (a cenotaph). The epitaphic inscription is compiled in honor of the chief of the Torkuz-oghuz tribe bughu (Chin. Pugu), who was a subject of the Tang Empire and as such can be seen a very important written source on the history of ancient Turkic period. Alongside with the analysis and interpretation of the accounts of the epitaph, the author discusses the meaning of the discovered in the same burial mound of a collection of wooden and ceramic burial small statuettes, which shows close relations between the Tokuz-oghuz tribes of the steppe with oases of Eastern Turkistan, where a center of manufacturing of burial inventories was located.